THE ROLE OF TEACHER SUPERVISION BY THE PRINCIPAL AT SMP COUNTRY 3 PERCUT SEI TUAN - Muhammad Azmi Tanjung; Lolia Purnama Sari; Najwa Al Fachrani; Aulia Zakiah; Amelia BR. Kaban (Journal of Quality Islamic Education Research, 2024)
The method used in this research is descriptive qualitative analytical. The descriptive method means that the researcher explains the real conditions of supervision carried out by the principal at SMP Caountry 3 Percut Sei Tuan, while qualitative analysis is used when researching the role of the principal's supervision in supervising teacher performance at  SMP Caountry 3 Percut Sei Tuan. The scope of this research is field research taking place at SMP Caountry 3 Percut Sei Tuan. Data collection techniques use interviews, documentation and observation. Data sources consist of primary data and secondary data. In conducting research, researchers themselves naturally act as research instruments. The data analysis techniques used by researchers are data analysis, data reduction, data interpretation and conclusions. The results of this research are that the implementation of supervisory duties includes elements, personal, material and operational. The performance of teachers at Percut Sei Tuan Public Middle School has demonstrated good performance standards.